Identifying LATS2 as a prognostic biomarker relevant to immune infiltrates in human esophageal squamous cell carcinoma - Zhu, Minqi; Liao, Guoran; Wang, Yuxuan; Mo, Junxian; Yi, Dunbo; Zhang, Yuhong; Xian, Lei (Frontiers in Genetics, 2022)
According to the TIMER database, large tumor suppressor 2 (LATS2) is differentially expressed in various tumors. However, the correlation between LATS2 and esophageal squamous cell carcinoma (ESCC) and the association between LATS2 and immune infiltration in ESCC remain unclear. Our synthetic research on LATS2 in ESCC revealed that the expression was low in esophageal squamous epithelium tissues, revealing the pernicious and adverse prognosis of ESCC. The Kaplan–Meier survival investigation pointed out that low LATS2 expression would result in an adverse prognosis. Biological investigation indicated that LATS2 was engaged in cell migration, adhesion, and junction. To further explore the relationship between LATS2 and tumor immunity, we utilized CIBERSORT to assess immune infiltration. The findings revealed that specimens with lower LATS2 expression showed higher immune infiltration, including T-cell follicular helper cells, M0 macrophages, M1 macrophages, and myeloid dendritic cell resting. An association investigation indicated that LATS2 was negatively relevant to immune checkpoints that restrain operative antitumor immune reactions. We also conducted immunohistochemical staining to explore the link between LATS2 expression and immunophenotype. The indicated association between low LATS2 expression and an immunophenotype is conducive to our understanding of ESCC mini-environments and might offer new indications for enhancing new therapeutic targets.